Disturbance and Control of National Strategic Gas Storage Induced by Adjacent Tunnel Blasting - Ma, Longhao; Lin, Fei; Liu, Rong; Liu, Peng; Xia, Guang; Chen, Lichuan (Frontiers in Earth Science, 2022)
Underground gas storage are often subject to external dynamic loads, blast vibrations, and seismic disturbances, since they function as backup areas for the strategic national energy reserve, supply and demand dispatch, and gas and energy storage. Currently, the research on dynamic response characteristics, dynamic stability, and disturbance control of underground gas storages under dynamic loads is still incomplete and of great practical importance to ensure national strategic security. Therefore, this paper takes the blasting project of the Sansheng tunnel, which passes through the national strategic gas storage reservoir, as the engineering background. Based on the geological conditions and rock characteristics, the dynamic response characteristics of the rock surrounding the tunnel and gas storage are studied using the finite element method. The peak vibration velocity distribution of the surrounding rocks at different blasting source distances is analyzed and compared with the theoretical formula. Subsequently, an asymmetric uncoupled blasting vibration control technique is proposed and used for field blasting. The results show that the numerical results are consistent with the theoretical formula. The blasting vibration velocity decreases exponentially with an increase in the blasting source distance. Overall, the proposed technique significantly decreases the average peak vibration velocity by 22.64% compared to the original vibration velocity.